2022
DOI: 10.1177/07356331211058662
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of MALL on L2 Pronunciation Learning: A Meta-Analysis

Abstract: Mobile-assisted language learning has emerged as a valuable tool for L2 pronunciation learning as it offers ample opportunities for learners to perform authentic learning activities anytime and anywhere. However, the extent to which mobile devices may facilitate or enhance L2 pronunciation has yet to be systematically investigated. To address the research gap, the study drew on a meta-analytic framework to examine the overall average effect of mobile devices on L2 pronunciation learning. The meta-analysis cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
3
14
1
Order By: Relevance
“…Moreover, the utilization of ASR technology in the context of L2 pronunciation instruction has been found to yield positive effects on learners’ confidence and motivation. By offering learners a sense of control over their learning process, ASR technology empowers them to actively engage in their pronunciation development ( Liakin et al, 2015 ; O’Brien et al, 2018 ; Tseng et al, 2022 ). The enhanced confidence and motivation experienced by learners when utilizing ASR technology can lead to increased engagement and persistence in their L2 learning endeavors ( Golonka et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the utilization of ASR technology in the context of L2 pronunciation instruction has been found to yield positive effects on learners’ confidence and motivation. By offering learners a sense of control over their learning process, ASR technology empowers them to actively engage in their pronunciation development ( Liakin et al, 2015 ; O’Brien et al, 2018 ; Tseng et al, 2022 ). The enhanced confidence and motivation experienced by learners when utilizing ASR technology can lead to increased engagement and persistence in their L2 learning endeavors ( Golonka et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Lord (2008) , a lot of language instructors believe that by providing additional instruction in the second language, pupils would learn to pronounce it on their own; other language instructors question whether it is essential to provide instruction in the segmental and supra-segmental phonological aspects of a language ( Thomson and Derwing, 2015 ). However, numerous strategies, such as corrective feedback and complete immersion learning, are brought to pronunciation training by technology devices ( Eskenazi, 1999 ; Luo, 2016 ; Tseng et al, 2022 ), leading to a development that goes beyond the boundaries of the classroom and allows students to have freedom and control over their language learning abilities ( Pennington, 1999 ; Thomson, 2011 ; O’Brien et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was conducted using a similar rubric by Kennedy and Trofimvich [30]. The components of the tool are rubric for oral reading fluency, monitoring and projecting progress in reading fluency instruction chart, oral presentation evaluation scale, and rubric for speaking assessment (pronunciation/diction, fluency, word choice, usage, ideas/meaning) [31].…”
Section: Tools and Scalesmentioning
confidence: 99%
“… Phetsut and Waemusa (2022) studied how teachers’ feedback on L2 learners oral exercise through WhatsApp helped learners to improve their oral accuracy. Tseng et al (2022) examined the overall average effect of mobile devices on L2 pronunciation learning by drawing on a meta-analytic framework. Their research results showed that the use of mobile devices had a significant effect on L2 pronunciation learning.…”
Section: Review Of the Literaturementioning
confidence: 99%